Geometric inaccuracy and co-registration errors for CT, DynaCT and MRI images used in robotic stereotactic radiosurgery treatment planning. (January 2020) - Aldosary, Ghada; Szanto, Janos; Holmes, Oliver; Lavigne, Bernie; Althobaity, Waleed; Sheikh, Adnan; Foottit, Claire; Vandervoort, Eric
Highlights: Geometric and coregistration errors were measured for multimodality SRS planning images. Three phantom designs (one commercial, and two in-house built) were compared. The commercial phantom with treatment planning software overestimates uncertainties on CT-based images. The highest uncertainties reported were for DynaCT, followed by MRI-T2 weighted images. The in-house built 3D printed phantom is suitable as a multimodality imaging QA tool. Abstract: Purpose: To measure the combined errors due to geometric inaccuracy and image co-registration on secondary images (dynamic CT angiography (dCTA), 3D DynaCT angiography (DynaCTA), and magnetic resonance images (MRI)) that are routinely used to aid in target delineation and planning for stereotactic radiosurgery (SRS). Methods: Three phantoms (one commercial and two in-house built) and two different analysis approaches (commercial and MATLAB based) were used to quantify the magnitude of geometric image distortion and co-registration errors for different imaging modalities within CyberKnife's MultiPlan treatment planning software. For each phantom, the combined errors were reported as a mean target registration error (TRE). The mean TRE's for different intramodality imaging parameters ( e.g., mAs, kVp, and phantom set-ups) and for dCTA, DynaCTA, and MRI systems were measured. Results: Only X-ray based imaging can be performed with the commercial phantom, and the mean TRE ± standard deviation values were large compared to the in-house analysis using MATLAB. With the 3D printed phantom, even drastic changes in treatment planning CT imaging protocols did not greatly influence the mean TRE (<0.5 mm for a 1 mm slice thickness CT). For all imaging modalities, the largest mean TRE was found on DynaCT, followed by T2-weighted MR images (albeit all <1 mm). Conclusions: The user may overestimate the mean TRE if the commercial phantom and MultiPlan were used solely. The 3D printed phantom design is a sensitive and suitable quality assurance tool for measuring 3D geometric inaccuracy and co-registration errors across all imaging modalities.